2020
DOI: 10.3390/min10090765
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of New Applications of Oil Shale Ashes in Building Materials

Abstract: Achieving sustainable zero-waste and carbon neutral solutions that contribute to a circular economy is critically important for the long-term prosperity and continuity of traditional carbon-based energy industries. The Estonian oil shale (OS) sector is an example where such solutions are more than welcome. The combustion of OS generates a continuous flow of ashes destined to landfills. In this study, the technical feasibility of producing monolith building materials incorporating different OS ashes from Estoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…98% of the ash production) landfilled [ 33 ]. The raw oil shale CFBC ash has weak pozzolanic and self-cementitious properties [ 34 , 35 , 36 ], but the ash has been studied for accelerated carbonation and alkali activation to improve the mechanical properties of the ash aggregates [ 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…98% of the ash production) landfilled [ 33 ]. The raw oil shale CFBC ash has weak pozzolanic and self-cementitious properties [ 34 , 35 , 36 ], but the ash has been studied for accelerated carbonation and alkali activation to improve the mechanical properties of the ash aggregates [ 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The oil shale ash (OSA) is the residual product of the direct burning of the oil shale [1]. This ash becomes more accepted as sub-alternative material in several industrial products manufacturing; especially in the ceramics, water treatment plants and construction materials [2][3][4][5][6] The latter use received massive interests in the last decade with the focus on the cement partial replacement in concrete [7][8][9]. Such replacement promotes reducing the need of high cement ratio in concrete with insignificant differences in the mechanical properties [8].…”
Section: Introductionmentioning
confidence: 99%
“…The percentages of the OSA replacement in cement vary between 10-30 percent [3,7]. These percentages along with mixing amounts will lead to different cement mixture and, thus, different mechanical properties [6]. Another research paper suggested up to 15% OSA replacement to produce typical Portland cement clinker.…”
Section: Introductionmentioning
confidence: 99%
“…By today, possibilities of using OS ash have been quite extensively studied and some have been realised (mainly based on outdated pulverised firing technology). The related areas are: production of cement and building blocks [18][19][20], preparation of curing mixtures and manufacturing of construction aggregates [21,22], road base construction and strengthening/stabilizing of peat ground arrays [23], backfilling of underground mines [24], quick neutralization of acidic soils and production of granulated soil conditioners with modified composition [25,26]. Oil shale is also utilised as a polymer filler, a raw material for precipitated calcium carbonate production [27][28][29], a component of ceramic plates and geopolymers [30], and materials with zeolitic properties, tobermorites [31][32][33], a phosphorus sorbent in municipal sewage treatment [34,35], and an acidic gases sorbent (CO 2 and SO 2 ) [36,37].…”
Section: Introductionmentioning
confidence: 99%